Editorial Introduction: East/West Dialogues in Buddhism - Davis, Leesa S. (Journal for the academic study of religion, 2016)
An introduction is presented in which the editor discusses articles in the issue on topics including Buddhism, Buddhist sociology and the book "Engaging Buddhism: Why It Matters to Philosophy" by Jay L. Garfield.